Sensor fusion in the epistemic situation calculus. Issue 5 (2nd September 2016) - Schwering, Christoph; Niemueller, Tim; Lakemeyer, Gerhard; Abdo, Nichola; Burgard, Wolfram
Abstract : Robot sensors are usually subject to error. Since in many practical scenarios a probabilistic error model is not available, sensor readings are often dealt with in a hard-coded, heuristic fashion. In this paper, we propose a logic to address the problem from a KR perspective. In this logic, the epistemic effect of sensing actions is deferred to so-called fusion actions, which may resolve discrepancies and inconsistencies of recent sensing results. Moreover, a local closed-world assumption can be applied dynamically. When needed, this assumption can be revoked and fusions can be undone using a form of forgetting.